Disability Advocacy in American Mainline Protestantism - Herzog, Albert A. (Journal of religion, disability & health, 2006)
This article provides a brief summary of the disability advocacy in seven American mainline Protestant denominations: the American Baptist Convention; Disciples of Christ; the Episcopal Church; the Evangelical Lutheran Church in American, Presbyterian Church USA; the United Methodist Church; and the United Church of Christ. This history covers the various ministries to the disabled from the pre-1950 era to more recent events including the work of disability advocacy after denominational reorganization.